Impact of diet on the immunological microenvironment of the pregnant uterus and its relationship to allergic disease in the offspring : a review of the recent literature - Moore, Daniella Campelo Batalha Cox; Elsas, Pedro Xavier; Maximiano, Elisabeth Santos; Elsas, Maria Ignez Capella Gaspar (São Paulo Medical Journal, 2006)
Medical progress has reduced the mortality from infectious diseases in most countries, but allergic diseases have become more prevalent worldwide over the same period, especially in industrialized countries. This has prompted speculation that modern lifestyles have altered the relationship between heredity and environ- ment so as to promote development of an atopic phenotype when exposure to infection decreases. A healthy uterine microenvironment is known to favor Th2 lymphocyte development. However, some evidence suggests that persistence of the Th2 pattern of immunity directs the developing organism’s immune response towards a long-last- ing atopic phenotype. Even though the outcome also depends on other factors (such as infection, functional state of the intestinal microflora, and exposure to environmental allergens at times critical to development), it seems that the immune system during the perinatal period is responsive to interventions that are no longer effective in adulthood. We have reviewed the literature accessible through Medline to identify recent advances in the prevention of allergic disease through interventions in the fetal-maternal relationship. Diet seems to have a significant impact on the immunological profile of the pregnant uterus, as well as on the postnatal development of allergic disease in the offspring, as suggested by the effects of probiotic bacteria and by manipulations of the dietary content of polyunsaturated fatty acids and antioxidants. This highlights the need for further studies, in order to define the best intervention methods, the most appropriate time interval and the individu- als who will most likely benefit from them.